Pemberitaan Politik Dinasti Presiden Jokowi Pada Pemilihan Presiden 2024 Di Media Online Tempo.Co Dan Tvonenews.Com (Analisis Framing Robert Mathew Entman) - Oktalisa, Nurul Eka; Nasution, Belli; Muchid (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2025)
This study is based on the issue of dynasty politics that emerged when President Joko Widodo was in power, with Gibran Rakabuming Raka, Jokowi's son, elected as Mayor of Solo in 2020, triggering speculation of dynasty politics and a possible candidacy as Vice President in 2024. This study aims to analyze two online media, tempo.co and tvonenews.com, in framing news before presenting it to the public and finding commodification in reporting on Jokowi's dynasty politics in the 2024 Presidential Election. The qualitative research method with data analysis techniques uses the Robert Mathew Entman framing model and Vincent Mosco's Commodification. The results of the research analysis found that the framing and commodification of online media, tempo.co and tvonenews.com, differ significantly in packaging and reporting news about Jokowi's dynasty politics in the 2024 Presidential Election. Tempo.co's framing focuses more on the social and ethical impacts of dynasty politics, with an emphasis on criticism of nepotism and the negative impacts that may arise for society in a democratic country. On the other hand, tvonenews.com framing focuses more on practical political aspects, including Gibran's candidacy steps and gives the impression that the issue of dynasty politics is commonplace and does not need to be a problem. Tempo.co's commodification focuses more on the quality of content and in-depth and critical analysis. While tvonenews.com's commodification focuses more on fast and sensational news to attract instant attention.